Biocidal Activity of Origanum vulgare subsp. hirtum Essential Oil - Milena Nikolova (Mendel University Press, 2021)
Toxic effect of Origanum vulgare subsp. hirtum (Link) Ietsw. essential oil was assayed on weeds (Lolium perenne L. Trifolium pratense L. and Trifolium repens L.), potato plants (Solanum tuberosum L.) and Myzus persicae Sulz. The GC-MS analysis of the essential oil revealed carvacrol as the main component. The essential oil solutions completely inhibited the seed germination of the target weeds at concentration 2 μL/mL in Petri dishes. In contrast, in soil, this effect was achieved at a concentration of 5 µL/mL for studied dicot and at 10 µL/mL for the monocot species. Total destruction of target weeds at post-emergence stage after spraying with solution of the essential oil in concentrate 10 µL/ mL was found. Mature potato plants were poorly affected by the essential oil. A completely toxic effect on M. persicae was established by applying a solution with a concentration of 3 μL/mL of the essential oil. The experimental data indicate that the essential oil of the species has great potential, as an alternative to synthetic biocides, for the production of eco-friendly formulations for pest control.